1998
DOI: 10.1002/(sici)1097-4652(199812)177:4<535::aid-jcp5>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Physiological signals and oncogenesis mediated through Crk family adapter proteins

Abstract: The viral Crk oncogene (v-Crk) is known to induce sarcomas in chicken and its cellular homologs c-Crk I, c-Crk II, and Crk-like (CRKL) have been implicated in many signal transduction events. These include cell differentiation, cell migration, and the induced nonresponsiveness of T-cells to stimulation of the T-cell receptor (TCR), a state known as anergy. CRKL is also the most prominent substrate of the Bcr-Abl oncoprotein which causes human chronic myelogenous leukemias (CML). The modular composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 154 publications
0
60
0
Order By: Relevance
“…20 Our hypothesis is that Rap1 could be activated in a similar manner in PV RBCs, HEL, and BaF3 JAK2V617F cells. Consistent with this hypothesis, Feller et al and Chin et al showed that Rap1 was activated by C3G and a member of the Crk family, CrkL, that is predominantly expressed in hematopoietic cells 36 and phosphorylated in response to stimulation with Epo or IL-3. 37 In their study, Arai et al showed that adhesion of the 32D hematopoietic cell line was activated by Epo or IL-3 through the activation of the C3G/CrkL complex, Rap1, and ␤ 1 integrins.…”
Section: Discussionmentioning
confidence: 76%
“…20 Our hypothesis is that Rap1 could be activated in a similar manner in PV RBCs, HEL, and BaF3 JAK2V617F cells. Consistent with this hypothesis, Feller et al and Chin et al showed that Rap1 was activated by C3G and a member of the Crk family, CrkL, that is predominantly expressed in hematopoietic cells 36 and phosphorylated in response to stimulation with Epo or IL-3. 37 In their study, Arai et al showed that adhesion of the 32D hematopoietic cell line was activated by Epo or IL-3 through the activation of the C3G/CrkL complex, Rap1, and ␤ 1 integrins.…”
Section: Discussionmentioning
confidence: 76%
“…CrkL itself is also inducibly phosphorylated on tyrosine residues [7,11,12]. The N-terminal SH3 domain of CrkL has been reported to interact with the guanine nucleotide exchange factors C3G and Sos, the kinases Abl and hematopoietic progenitor kinase 1 (HPK1), DOCK180, and Wiskott-Aldrich syndrome protein (WASP) [3, [13][14][15][16][17][18]. CrkL is expressed at high levels in hematopoietic cells [19] and has been linked to signaling via the T cell receptor (TCR), the B cell receptor, CD2, and integrins, as well as receptors for the cytokines IL-2, IL-3, IL-5, erythropoietin, thrombopoietin, IFN- § , IFN-+ , hepatocyte growth factor (HGF), and § -chemokines [10,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Crk interacts with phosphatidylinositol kinase, activating Akt [49], which also influences cancer cell adhesion in response to pressure [7]. Our results indicate that paxillin phosphorylation in human colon cancer cells in response to pressure facilitates paxillin-Crk binding, which is also required for the stimulation of adhesion.…”
Section: Discussionmentioning
confidence: 74%